Studying of the Pinus brutia Ten forest birds in relation to vegetation characteristics in Alfronloq protected area- Latakia - Alcheikh, Basima; Dayyoub, Maher (Latakia University Journal -Biological Sciences Series, 2013)
Pinus brutia cover 67.87% of AlFronloq protected area, this forest provide habitat for wildlife especially forest birds. The aim of this study is to define bird species that use Pinus brutia forest and their relation to vegetation characteristics.We listed 63 bird species, 9 of them recorded for first time, 31.8% of species are resident in study area, where raptors presented 15.9%. The study showed positive correlation between species richness and plant richness (R=0.588, P= 0.007). Shrubs layer coverage and richness affected positively bird species richness and density. The study showed also decreasing of bird species richness with Altitude, while raptors richness were increased with Altitude.The dominat species were Coal tit Parus ater, wren Troglodytes troglodytes ,whereas species like Chaffinch Fringilla coelebs, chiffchaff Phylloscopus collybita were the most abundant.